Chapter 2. INFORMATION COMPONENT OF THE WORK OF DIPLOMATIC MISSIONS IN THE INFORMATION AGE - Таміла ГРАЧЕВСЬКА (Епістемологічні дослідження у філософії, соціальних і політичних науках, 2024)
The role of diplomatic missions in the process of collecting, analysing and disseminating information was analysed. Particular attention was paid to the reasons and factors that radically changed the approaches and principles of information management by diplomatic missions in the twentieth and twenty-first centuries. The legal framework (international and national) for the implementation of the information function by diplomatic missions has been established. It is found that in order to optimise the information function, diplomatic missions actively use the latest information and communication technologies.  The author focuses on the forms of diplomatic missions' activities in which the information component plays an important role. The leading principles of organisation of information and analytical work in diplomatic missions are considered.  The author describes the types of information and reference documents prepared by the staff of diplomatic missions.  The author highlights the peculiarities of working with citizens' appeals and information requests, which is an important component of the work of diplomatic missions in modern conditions. The main forms and tools of outreach work of diplomatic missions in the countries of their residence are outlined.